Analysis of the ecological status of urban parks with emphasis on forest parks using GIS (Case study: Tabriz) - Hassan Mahmoodzadeh; musa vaezi; rahimeh rostami; maedeh bakooyi (تحقیقات کاربردی علوم جغرافیایی)
Considering the unfavorable environmental conditions of cities, the shortage and defects of open and green spaces in metropolitan cities, the need to pay attention to parks and green spaces of the city in terms of ecological and social functions of these spaces has been discussed more than before. For this purpose, this research has been investigated. And ecological analysis of regional parks in Tabriz city. The present research is analytical-descriptive in terms of its purpose. The information was collected in both documentary and field and analyzed using the GIS. The statistical population of the study is Tabriz Parks and Samarkand Pars in Tabriz, including Eagly Parks, Bagh Misha, Shams Tabrizi and Eram Parks. The methods and tools used for collecting and analyzing information in this research are questionnaire, ARC.GIS software, ANP network analysis method and MC-SDSS function and SAW method in GIS. Evaluating ecological indicators in four major axiological areas and ecological, environmental, cultural-educational and access design. For these indicators, criteria have been considered. Using the questionnaire, the importance of these criteria was obtained and the weight of the criteria was calculated by ANP method. In the studied parks, according to the results of the geological survey, the Eagle Park is in ecological terms, and the Shams, Baghmehisheh and Eram parks are in the next ranks, and the point is the inappropriate situation of the Eram Park and Baghmehisheh Parks, especially Eram, in comparison with other parks. It needs to adopt appropriate policies in this regard to improve its situation.